Penilaian Tingkat Kesehatan Koperasi Peternak Sapi Bandung Utara Menggunakan Rasio Keuangan - Rizkya Novianka; Suji Abdullah Saleh (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The North Bandung Farmers Breeders Cooperative (KPSBU) was formed to help dairy farmers in the North Bandung area. Cooperatives as a company (cooperative enterprise) require periodic performance appraisals in accordance with their achievements. This study aims to determine the level of financial health of cooperatives. The purpose of this study was to analyze the health level of cooperatives based on the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises number 06/Per/Dep.6/IV/2016. The aspects studied are capital aspects, productive asset quality aspects, efficiency aspects, and liquidity aspects. The method used in this research is descriptive method with data collection techniques in this study are financial reports, interviews and documentation. Based on the analysis results, the total assessment score obtained by KSPBU in 2016 obtained a score of 48.75, in 2017 there was an increase of 49.75. Meanwhile, for the years 2018-2020, the score was 48.75. The total score of the financial performance is in the range of 42.9 x < 52. So it can be concluded that the health of the financial performance of the KPSBU for the last five years has received the title